2020
DOI: 10.3389/fpsyg.2020.01264
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Impact of Internet-Based Instruction Integrated Innovation Education on University Student Entrepreneurial Team Collaboration and Strategic Innovation

Abstract: With the advent of knowledge economy, the competition of comprehensive national power gradually has shifted to talent competition. The cultivation of innovative talents and the incubation of student entrepreneurial teams are the primary educational goals of universities, which is an important part of the national innovation system. University student entrepreneurial teams present the attribute of high technology and unique knowledge advantage. The persistent innovation of student entrepreneurial teams is attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…A high completion rate for group tasks demonstrates teamwork. In other words, biology students trained using the IIETC method have high levels of cohesion on campus ( Zhao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A high completion rate for group tasks demonstrates teamwork. In other words, biology students trained using the IIETC method have high levels of cohesion on campus ( Zhao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of the entrepreneurial atmosphere will bring a group effect with the strengthening of entrepreneurial motivation of college students, which will raise the entrepreneurial enthusiasm of the students in sports majors (Yuan and Wu, 2020 ). Through entrepreneurial practice, Zhao et al ( 2020 ) found that the recognition of entrepreneurial behavior attitude, the accumulation of entrepreneurial behavior control, and the continuous strengthening of entrepreneurial subjective norms promote entrepreneurs to continue to learn and improve. To meet the market demand, it is required that government policy supply should be timely and effective, and there should be neither “vacancy” nor “dislocation,” to form a virtuous circle interaction between entrepreneurial conditions and entrepreneurial atmosphere (Zheng et al, 2018 ).…”
Section: Research Results and Analysismentioning
confidence: 99%
“…As mentioned above in detail, the vast majority of the literature implicates innovation in being involved as a part of a strategy that built on the fundamental notion of organizational sustainability. Strategic innovation can be utilized by organizations through the definition and adjustment of their operational scope; the creation and accumulation of core resources, and the construction and strengthening of their corporate networks [45,46]. In addition, as many various categories of strategies are increasingly being applied, organizations are seeking more practical methods to make sense of what innovations they can postulate.…”
Section: The Connection Between Strategic Innovation and Organization...mentioning
confidence: 99%